Differences in the Conformational Energy Landscape of CDK1 and CDK2 Suggest a Mechanism for Achieving Selective CDK Inhibition. Issue 1 (17th January 2019) - Wood, Daniel J.; Korolchuk, Svitlana; Tatum, Natalie J.; Wang, Lan-Zhen; Endicott, Jane A.; Noble, Martin E.M.; Martin, Mathew P.
Summary: Dysregulation of the cell cycle characterizes many cancer subtypes, providing a rationale for developing cyclin-dependent kinase (CDK) inhibitors. Potent CDK2 inhibitors might target certain cancers in which CCNE1 is amplified. However, current CDK2 inhibitors also inhibit CDK1, generating a toxicity liability. We have used biophysical measurements and X-ray crystallography to investigate the ATP-competitive inhibitor binding properties of cyclin-free and cyclin-bound CDK1 and CDK2. We show that these kinases can readily be distinguished by such inhibitors when cyclin-free, but not when cyclin-bound. The basis for this discrimination is unclear from either inspection or molecular dynamics simulation of ligand-bound CDKs, but is reflected in the contacts made between the kinase N- and C-lobes. We conclude that there is a subtle but profound difference between the conformational energy landscapes of cyclin-free CDK1 and CDK2. The unusual properties of CDK1 might be exploited to differentiate CDK1 from other CDKs in future cancer therapeutic design. Graphical Abstract: Highlights: Demonstration that ATP-competitive inhibitors distinguish cyclin-free CDK1 from CDK2 Determination of the first cyclin-free CDK1-ATP inhibitor complex structures Targeting cyclin-free CDKs may offer a clear selectivity window over CDK1 Abstract : Current CDK2 small-molecule inhibitors also inhibit CDK1, generating a toxicity liability. Biophysical measurements demonstrate that structurally diverse ATP-competitive inhibitors discriminate between monomeric CDK1 and CDK2. The unusual properties of monomeric CDK1 might be exploited to differentiate CDK1 from other CDKs in future cancer therapeutic design.